Online Quality Detection System for Gear based on Machine Vision - Xiaojin Wu; Wencheng Wang (Jixie chuandong)
In view of the problems existing in the defects detection for gear， a design scheme of the on-line detection system is proposed based on machine vision， and the functions such as image acquisition and display， image analysis and operation control are realized. The system controls the feeding equipment and the conveyor belt through the MCU control module， and using the photoelectric switch to trigger the high-speed camera to collect the image of the gear in real time. Then， by the industrial control machine preprocesses， the appearance quality information of the gear is obtained. Finally， the outputted signals of NG and OK are transmitted to the single chip computer to realize the sound-light alarm and sorting. Experiments show that the method has high accuracy and efficiency， and can meet the needs of actual production. It provides a new way for on-line measurement of gear.